2016
DOI: 10.18632/oncotarget.13032
|View full text |Cite
|
Sign up to set email alerts
|

The induction of autophagy against mitochondria-mediated apoptosis in lung cancer cells by a ruthenium (II) imidazole complex

Abstract: In the present study, it was found that the ruthenium (II) imidazole

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 70 publications
3
41
1
Order By: Relevance
“…These results indicated that autophagy could activate apoptosis in luteolin treated HCC cells. On the one hand, our result conflicted with certain previous studies that indicated that autophagy could suppress apoptosis in certain physiological process of cancer [34, 35]. On the other hand, our results were supported by other studies that indicated that autophagy could promote apoptosis in certain physiological process of cancer [36, 37].…”
Section: Discussioncontrasting
confidence: 95%
“…These results indicated that autophagy could activate apoptosis in luteolin treated HCC cells. On the one hand, our result conflicted with certain previous studies that indicated that autophagy could suppress apoptosis in certain physiological process of cancer [34, 35]. On the other hand, our results were supported by other studies that indicated that autophagy could promote apoptosis in certain physiological process of cancer [36, 37].…”
Section: Discussioncontrasting
confidence: 95%
“…50,51 MAPK pathway can regulate many cellular processes, cell proliferation, apoptosis and differentiation, 52 which can be modulated by ROS-dependent redox cycling. [53][54][55] Therefore, we speculated that MAPK pathway might be involved in the regulation of 7-KC-induced apoptosis by autophagy. In our study, 7-KC significantly induced activation of MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…132 The process of autophagy is regulated by autophagy-related (ATG) proteins and the role of autophagy in cancer is complex and is contextually dependent. 136 For example, autophagy can inhibit or facilitate cell death. The process of necrosis differs from the apoptosis in a number of ways.…”
Section: Cell Death Processmentioning
confidence: 99%